2019
DOI: 10.1111/eea.12794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat shock on survival and predation of an important whitefly predator,Serangium japonicum

Abstract: Climate change is expected to increase the frequency of periods of extreme weather events, including heat waves that are harmful to arthropod natural enemies. We studied the thermotolerance of the ladybeetle Serangium japonicum Chapin (Coleoptera: Coccinellidae), an important native predator of the whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) in China. Serangium japonicum eggs, first‐ and fourth‐instar larvae, pupae, and adults were subjected to a range of high temperatures (36, 39, 42, 43.5, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…2, 24,25 For example, Bemisia tabaci Q (Hemiptera: Aleyrodidae) is more heat tolerant than its predaceous coccinellid Serangium japonicum (Coleoptera: Coccinellidae), which may reduce the biological control of B. tabaci by S. japonicum in a warming world. 26 In natural ecosystems, insects often experience diel temperature fluctuations rather than constant temperatures. Moreover, daily maximum temperatures do not occur alone, but high temperatures on 1 day are often associated with high temperatures on subsequent days, leading to heat waves that may last for days, and short periods of extreme temperatures separated by sufficiently long periods of normal temperatures may allow insects to recover before each hot wave.…”
Section: Introductionmentioning
confidence: 99%
“…2, 24,25 For example, Bemisia tabaci Q (Hemiptera: Aleyrodidae) is more heat tolerant than its predaceous coccinellid Serangium japonicum (Coleoptera: Coccinellidae), which may reduce the biological control of B. tabaci by S. japonicum in a warming world. 26 In natural ecosystems, insects often experience diel temperature fluctuations rather than constant temperatures. Moreover, daily maximum temperatures do not occur alone, but high temperatures on 1 day are often associated with high temperatures on subsequent days, leading to heat waves that may last for days, and short periods of extreme temperatures separated by sufficiently long periods of normal temperatures may allow insects to recover before each hot wave.…”
Section: Introductionmentioning
confidence: 99%
“…The positive impact of air temperature on mortality due to natural enemies may be because of their enhanced ability to suppress pest populations under the temperature ranges observed (Huang et al, 2008). Under warmer temperatures, higher parasitoid reproductive success (Zilahibalogh et al, 2009;Romo & Tylianakis, 2013;Kambrekar et al, 2015) and greater survival of coccinellids (Simmons & Legaspi, 2004;Huang et al, 2008;Yao et al, 2019) have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Even if these thermal tolerance metrics have been linked to the geographical distribution in Drosophila species [ 12 , 34 ], it has been suggested that such simple measures can lack an assessment of biologically relevant performance [ 33 , 35 ]. The performance of mobility and behavioural traits, including walking, flying, and fitness traits such as mating behaviour, may be more ecologically relevant and driven by environmental temperatures, unlike those that drive endpoint traits [ 36 , 37 ]. Furthermore, studies have shown that mobility and behavioural traits show effects of acclimation or hardening treatments not seen when using endpoint metrics in traditional stress tolerance assays [ 22 , 38 ].…”
Section: Discussionmentioning
confidence: 99%